2011
DOI: 10.1111/j.1600-0404.2011.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

The Creutzfeldt-Jakob disease (CJD) neurological status scale: a new tool for evaluation of disease severity and progression

Abstract: Objectives-To develop a scale sensitive for the neurological manifestations of CreutzfeldtJakob disease (CJD).Methods-A 26-item CJD neurological status scale (CJD-NS) was created based on characteristic disease manifestations. Each sign was assigned to one of eight neurological systems to calculate a total scale score (TSS) and a system involvement score (SIS). The scale was administered to 37 CJD patients, 101 healthy first-degree relatives of the patients and 14 elderly patients with Parkinson's disease (PD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…These results are in good agreement with a recent CJD neurological status scale developed to assist in distinguishing sCJD patients [25]. While sCJD may sometimes have a predilection for the cerebellum, MRI methods such as DWI may be insensitive to abnormalities in these regions [26].…”
Section: Discussionsupporting
confidence: 81%
“…These results are in good agreement with a recent CJD neurological status scale developed to assist in distinguishing sCJD patients [25]. While sCJD may sometimes have a predilection for the cerebellum, MRI methods such as DWI may be insensitive to abnormalities in these regions [26].…”
Section: Discussionsupporting
confidence: 81%
“…In this study in a unique population of patients with fCJD, we showed a significant positive correlation between CSF tau levels and various measures of disease severity. The highest correlation was evident for our newly developed CJD‐NDS which although not specific to CJD is based on evaluation of the dysfunction in several neurological systems and reflects the versatility of the clinical symptoms in this disorder. In addition, we also found a significant negative correlation between tau levels in the CSF and the cognitive performance as reflected by the MMSE and FAB scales.…”
Section: Discussionmentioning
confidence: 92%
“…All patients were examined by a neurologist who performed several tests including the minimental state examination (MMSE) , the frontal assessment battery (FAB) , the expanded disability status scale (EDSS) , the NIH Stroke Scale (NIHSS) , and the CJD‐NS .…”
Section: Methodsmentioning
confidence: 99%
“…Sensation was intact and the gait was ataxic. She scored 27/30 on the Mini‐Mental State Examination (MMSE) (communicated in writing) and her score on the CJD neurological status scale (CJD‐NS) was 10 (range 0–52).…”
Section: Resultsmentioning
confidence: 98%